TECHNOLOGİCAL CİTİZENSHİP AND THE RİSK PERCEPTİONS REGARDİNG COMMERCİALİZATİON OF HUMAN GENETİCS (Third Sector Social Economic Review, 2011)
In this study, the risk perceptions of the consumers of the health care service regarding human genetics products and applications have been analyzed; technology and biotechnology policies have been assessed. Health care service implementers are consumers as well as the people who benefits from the health service. Therefore they both benefit from technological citizenship in the context of medical biotechnology. In this review it has been dwelled upon the risk of commercialization of the human genetics. The regulations related to the biotechnology and biosafety in Turkey and the technological citizenship as a state of citizenship in the context of the rights and the responsibilities have been evaluated. The consequences and the suggestions have been stated about technological citizenship and human genetics products and applications.
Keywords: technological citizenship; human genetics; the risk of commercialization; medical biotechnology; consumer of the health care service